2011
DOI: 10.1089/end.2010.0269
|View full text |Cite
|
Sign up to set email alerts
|

Single-Site Video Endoscopic Inguinal Lymphadenectomy: Initial Report

Abstract: Techniques that attempt to further reduce the morbidity and improve cosmesis of laparoscopic surgery have particularly generated interest. Since its initial urologic description in 2007, there has been a surge of interest in laparoendoscopic single-site surgery, which is now an emerging technique within the field of minimally invasive urologic surgery. This report describes a preliminary experience with single-site video endoscopic inguinal lymphadenectomy (SSVEIL) compared with conventional video endoscopic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 11 publications
0
20
0
1
Order By: Relevance
“…Tobias‐Machado et al. showed that LESS inguinal lymphadenectomy could provide better aesthetic results than conventional endoscopic inguinal lymphadenectomy. This conclusion was confirmed by our preliminary results; nine patients (75%) preferred the postoperative cosmetic results found in the limb that underwent LESS inguinal lymphadenectomy than those of their contralateral limbs that underwent conventional endoscopic inguinal lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tobias‐Machado et al. showed that LESS inguinal lymphadenectomy could provide better aesthetic results than conventional endoscopic inguinal lymphadenectomy. This conclusion was confirmed by our preliminary results; nine patients (75%) preferred the postoperative cosmetic results found in the limb that underwent LESS inguinal lymphadenectomy than those of their contralateral limbs that underwent conventional endoscopic inguinal lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…For the LESS inguinal lymphadenectomy procedure (total 12 limbs), a skin incision of 2.5 cm was made 2 cm distal to the lower vertex of the femoral triangle . After blunt finger dissection, a domestic multi‐access platform (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of lymph nodes harvested is comparable with open inguinal lymphadenectomy [18,23,26,29,30] and with the advantage of less subcutaneous flap injuries and attendant complications, shorter hospitalization, and early patient ambulation and recovery [17,[23][24][25][26][29][30][31]. Our operating time was significantly longer compared to classical surgery, but we believe that standardized surgical procedures, improvements of endoscopic instrumentation, and a dedicated trained surgical team could considerably improve this aspect.…”
Section: Resultsmentioning
confidence: 95%
“…In 2006, Tobias-Machado et al [17] published an initial case report of video endoscopic inguinal lymphadenectomy compared with a controlateral open radical procedure. VEIL continues to evolve: single site and robotic variants were recently presented [18][19][20].…”
Section: Introductionmentioning
confidence: 99%